Quantification of biventricular strain and assessment of ventriculo–ventricular interaction in pulmonary arterial hypertension using exercise cardiac magnetic resonance imaging and myocardial feature tracking. Issue 5 (24th October 2018) - Lin, Aaron C.W.; Seale, Helen; Hamilton‐Craig, Christian; Morris, Norman R.; Strugnell, Wendy
Abstract : Background: Right ventricular (RV) failure is the main cause of mortality in pulmonary arterial hypertension (PAH). Exercise testing helps identify early RV maladaptation and systolic dysfunction and facilitates therapy. Myocardial strain has been shown to be more sensitive than ejection fraction (EF) in detecting subclinical ventricular contractile dysfunction. Chronic pressure overload in PAH had been associated with changes in left ventricular (LV) filling. Purpose: To compare biventricular strains and ventriculo–ventricular interaction in PAH and controls using cardiac magnetic resonance feature tracking (cMRI‐FT) and to determine the reproducibility of strain analysis. Study Type: Prospective. Population: Nine PAH and nine control subjects. Field Strength/Sequence: 1.5T MRI balanced steady state free precession. Assessment: RV and LV longitudinal strain (EllRV and EllLV ) were derived using the mid‐axial images. Radial (ErrLV ) and circumferential strain (EccLV ) were derived using the mid‐ventricular short‐axis images. Relationships between strain and volumetric parameters were assessed at rest and during submaximal in‐magnet exercise. Statistical Tests: Comparison of rest‐to‐exercise data between PAH and controls was analyzed using two‐way repeated measures analysis of variance. The relationship between volumetric parameters and cMRI‐FT were assessed using Pearson's correlation. Reproducibility was assessed by using Bland–Altman plots. Results: PAH had significantly lower EllRV at rest (−16.6 ± 2.7 vs. −20.1 ± 3.6, P  = 0.03) despite normal RVEF. During exercise, RV systolic contractile reserve measured by EllRV was significantly reduced in PAH ( P Interaction  = 0.02). In PAH, indexed RV end‐systolic volume (ESVi) significantly correlated with EccLV and ErrLV at rest ( r  = −0.65 and r  = −0.70, P < 0.05) and with ErrLV during exercise ( r  = −0.43, P < 0.05). High observer agreement was demonstrated. Data Conclusion: Despite normal resting RVEF, RV systolic function and contractile reserve as measured by EllRV was significantly reduced in PAH. The close relation between RVESVi with EccLV and ErrLV provides evidence of systolic ventriculo–ventricular interaction in PAH. Exercise cMRI‐FT may provide a quantitative metric for detection of subclinical RV dysfunction in PAH. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:1427–1436.